Quality and Competitiveness in the System of Higher Education: Aspects of Interrelation - A. I. Vasil’ev (Высшее образование в России, 2019)
The article examines the relationship between the theoretical categories “quality of education” and “competitiveness of education”, as applied to educational activities of higher educational institutions. Based on a review of the scientific literature, the author adduces the examples of the opposition and mixing of the quality and competitiveness of education. The quality of education and its competitiveness are characterized as fundamental values that are the objects of analysis and evaluation in the university management system. The author’s definition of the competitiveness of educational organization as a feature reflecting the relative superiority over rivals at the pre-active stage is proposed. The author considers the relationship of competitiveness and quality of education by highlighting the methods and indicators of their evaluation and analysis in the intra-university management system. The mutual dependence of the quality and competitiveness of education is manifested in the formulation of indicators and methods for their evaluation. Assessment of the competitiveness of education and evaluation of its quality have a methodological commonality – using assessment approaches based on the “resource” and the “resultant” methodology. It has been proved that when evaluating the competitiveness of education, the results of educational activities should be taken into account, and using only an approach focusing on the resources of educational activities to assess the competitiveness of education will make such an assessment incomplete. The “quality” – “competitiveness” matrix built by the author allows to reveal four types of universities.